Pengembangan Pembelajaran Berbasis Teknologi melalui Media Video Pembangkit Listrik Tenaga Air (PLTA) - Christin Hutagaol; Jenice Fausta Ro Intan Sagala; Fathan Muninan Sugiatna; Fakhri Malikal Azis; Dzikri Fahreza N; Didik Aribowo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
By utilizing Hydroelectric Power Plant (PLTA) video media as a learning resource, this study aims to develop technology-based learning by using various material sources, including images, animations, and videos collected from the internet, to create video media that is more focused and suited to students’ needs. This research is motivated by the importance of technology-based learning media in supporting a learning process that is more engaging, interactive, and easier for students to understand. In addition, with the rapid development of digital technology, innovative learning media must be utilized to prevent learning from becoming monotonous and to increase the audience’s interest in the material being studied. The PLTA video media was developed as an alternative learning medium that presents material visually and systematically, helping audiences understand the working process of a hydroelectric power plant more easily. Furthermore, the use of video media is expected to assist teachers in delivering learning materials in a more creative and modern way, so that the learning process can run more effectively and in accordance with current developments in educational technology.